RETRACTED: Retrospective assessment and forecast of the level of development of intelligent transport infrastructure (using the example of JSC Russian Railways) - Egorov Y.; Fedorova M. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001